The first piece passes through the points (-6,-9) and (-1,-4) so the equaton of first piece is:
![\begin{gathered} (y+9)/(x+6)=(-4+9)/(-1+6) \\ y+9=x+6 \\ y=f(x)=x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8lb76m5dgwcmz1yd94c6eesbimg6yriu8n.png)
The second piece passes through the points (2,-5) and (3,-6) so it follows:
![\begin{gathered} (y-(-5))/(x-2)=(-6-(-5))/(3-2) \\ y+5=-x+2 \\ y=f(x)=-x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dtpjainogie9llc3rs54n9syqx5rxhzqrz.png)
Hence the piecewise function is given by:
[tex]f(x)=\begin{cases}x-3,-6\leq x<1 \\ -x-3,1
The above function is the required piecewise function.